Methodological guidelines of training and its impact on the interdisciplinary work of teachers at the middle level of the San Pio X educational Unit - Cañar Yumbolema, Darwin Danilo (Tierra Infinita, 2022)
The present investigation deals with the study of the methodological guidelines of training and its incidence in the interdisciplinary work of the teachers of the middle basic level of the “San Pio X” Educational Unit, in addition, the theoretical foundation of the methodological guidelines of training in the teaching process. learning, in the same way, the interdisciplinary work of teachers is argued epistemologically. Also, it is determined if the methodological training guidelines affect the interdisciplinary work of teachers. Likewise, a proposal was designed to solve the problem raised. It should be noted that the survey was applied to 21 teachers and 120 students, the students’ responses were taken as a point of reference to have a clearer, more coherent and transparent perspective. In the same way, the statistical model of chi2 was applied, the result was obtained (47.16488), which allowed us to accept the alternative hypothesis (H1) that says that “The methodological guidelines of training SI affect the interdisciplinary work of the teachers of the medium basic level. For this reason, the objective of the proposal is to train teachers in the different technological media, such as virtual classrooms, since it is a technological medium, where the teacher will self-train about the LOEI regulations, methodological guidelines for training, quality standards, school coexistence, discipline management within the classroom for quality education and warmth.